Legislasi Hukum Islam di Kerajaan Demak (Studi Naskah Serat Angger-Angger Suryangalam dan Serat Suryangalam) - Anafah, Naili (Fakultas Syariah IAIN Purwokerto, 2011)
Learning the history of law and establishment and also the changing of legislation regulation in pre-colonial period is an interesting thing and hoped to be able to give input for the experts of Indonesia law in the frame work of rearrangement Indonesia law system. We will get description how the type of legislation regulation which prevails in Indonesia before Dutch held invention of law when Dutch was colonizing Indonesia. This article will find various guidelines to the understanding that the literature of java is and important source for the history of development islam law in Indonesia.The writer will examine the manuscript of law which was created in Demak kingdom period, that was serat angger-angger and suryangalam and serat suryagalam. This article will discuss how the setting of sosio cultural and the politics of Demak kingdom as the place which was what forms the background of appearing the manuscript of serat angger-angger. The writer finds the law principles in serat angger-angger suryangalam and serat suryagalam